A prática da educação física no ensino médio : percepções dos alunos sobre a esportivização e formação - Fasolin, Marcos Antonio (2020)
This dissertation seeks to reflect on the role of Physical Education in the education of students, considering the proposals of the new BNCC (2017). The questioning arose as a result of the fact that PE classes in high school are generally limited to teaching sports, such as soccer, futsal, volleyball, handball and basketball. The problem is not only the aspect of sports choices, but mainly about the destination of the purpose of physical education to competition (sports). This has led many students to understand Physical Education classes as the practice of a sport. The study analyzes the behavior of young people and adolescents in their effective participation in Physical Education classes, verifying if the activities developed favor the students' understanding of their own body and its possibilities, as well as if they are committed to the students' quality of life. The reasons that lead young people and adolescents to not participate actively in Physical Education classes are identified and analyzed, as well as the comprehensions and attitudes of the students in front of the classes developed. Special attention is given to students who do not present sports skills during classes and the reasons they indicate justifying the demotivation and the little effective participation in the classes taught in High School. The hypothesis of the dissertation is that the discipline of Physical Education can enable, perhaps, more than the others, a significant change in the teaching-learning process and in the integral formation of the individual. This dissertation is anchored in the qualitative research approach and wishes to do justice to the complexity of reality. We follow this methodology mainly because we believe that through it we can become more aware, because we are motivated to criticize and analyze with consistency and thus explore more deeply the circumstances to be studied. Part of our study sample was 484 high school students, from two public schools in the city of Pato Branco-PR. The data collection was done through a structured questionnaire, applied by the researcher himself in class. The results point to the predominance of sports, but also that, even so, many students attribute to the subject of Physical Education an important role in their education, especially in the development of a good quality life. The conclusion points to the need for reorganization of subjects and the introduction of more appropriate ways of teaching the classes so that the student feels pleasure and reaches a more integral development in Physical Education.